Garlic in vitro culture for clonal recovering virus-free plants (Revista de Ciências Agroveterinárias, 2011)
Viral diseases have been promoting significant losses in garlic plant production. The main strategy to overcome these problems has been the use of healthy propagation material obtained by tissue culture. The initial procedure for producing garlic in vitro consists in choosing bulbs of larger size and better phytossanitary aspect. After the cloves are vernalizated and submitted to thermotherapy. From this material, the explants are excised and inoculated in MS medium under concentrations of inductor growth regulators, in order to promote in sequence shoot, rooting and in vitro bulbification. The obtained microbulblets are vernalizated and acclimatized at a protected environment. A posteriori, the obtained plantlets are indexed to the main viruses that infected the culture. This process is repeated until the material is clearly virus-free. Finally, these materials are multiplied in field conditions and distributed to “seed” farmers. It was concluded that in vitro garlic culture is the main method employed for clonal recovering virus-free plants.
Keywords: Allium sativum L.; Micropropagation; Acclimatization and indexing.